Keunggulan Pembiayaan Multiguna UMKM dengan Penerapan Akad Murabahah di PT. Bank Syariah Indonesia KCP Simalungun Perdagangan: Multiguna - Imam Hamdani; Ahmad Amin Dalimunthe (STEI Kanjeng Sepuh Gresik Jawa Timur, 2022)
The sharia trade used is a murabahah contract. The justification behind this discussion is to sort out what are the potential benefits of multipurpose financing, to sort out the procedures for providing multipurpose financing to micro, small and medium enterprises through murabahah contracts. Research conducted by the manufacturer at PT. BSI Kcp Simalungun Trading .district. The results and conclusion of the discussion show that PT. BSI Kcp Simalungun Trading has multipurpose financing that is given to small, almost non-existent and medium scale businesses to increase business capital that has been sympathetic for no less than one year and has taken advantage of multipurpose financing in assisting financing applications for clients and assisting two players. The movement of resources introduced by multipurpose financing is colossal, up to 500 million to be exact with the use of murabahah contracts.